Fatigue responses during repeated sprints matched for initial mechanical output - Mendez-Villanueva, A.; Hamer, P.; Bishop, D. (Medicine & Science in Sports & Exercise, 2007)
Purpose: To compare muscle fatigability during two sets of repeated cycling sprints matched for initial mechanical output in a nonfatigued and fatigued state.